Femoral Hypoplasia-Unusual Facies Syndrome: A Case Report - Hoque, Mujibul; Ali, Md Manajjir; Mia, Mohammed Abdul Hai; Ali, Syed Mortaza (Journal of Bangladesh College of Physicians and Surgeons, 2016)
The femoral hypoplasia-unusual facies syndrome (FH-UFS) is a very rare association of femoral and facial abnormalities. We report a 19 days old male baby with bilateral femoral hypoplasia and cranio-facial dysmorphism including low set ears, upslanted palpebral fissures, long philtrum with thin upper lip, micrognathia, hypoplastic alae nasi, short broad tipped nose, and cleft palate. Tongue tie was also present as an additional feature. J Bangladesh Coll Phys Surg 2015; 33(4): 229-231